INTEGRATING CAPACITY-BASED MITIGATION PARADIGMS AND SUSTAINABLE DEVELOPMENT GOALS (SDGs) INTO RESILIENT URBAN SPATIAL PLANNING : A CASE STUDY OF THE NOVEMBER 2025 HYDROMETEOROLOGICAL CRISIS IN LANGSA CITY - Fildzah, Cut Nur Nabilah; Wulandari, Elysa; Rizki, Muhammad; Nabila, Selyana (Center for Environmental Studies, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Langsa City faces escalating challenges from hydrometeorological disasters that threaten socio-economic stability, as evidenced by the extreme flooding event on November 26, 2025. This study aims to formulate an integration model between local spatial planning policies (RDTR/RTRW) and capacity-based disaster mitigation paradigms within the Sustainable Development Goals (SDGs) framework, specifically Goal 13 (Climate Action). Employing a descriptive qualitative method with a spatial approach, this research identifies infrastructure vulnerabilities and socio-economic impacts across five districts. Spatial analysis reveals that rice field land cover in Langsa dropped from 2,410 hectares in 2012 to 1,925 hectares in 2025, representing a significant loss of natural water retention. Analysis of the November 26, 2025, event reveals spatial anomalies where floodwaters encroached into zones previously categorized as